LINGKAR PINGGANG DAN ADIPONEKTIN PADA REMAJA OBESITAS Waist Circumference and Adiponectin in Obese Adolescents - Nur Aisiyah Widjaja; Rendi Aji Prihaningtyas; Meta Herdiana Hanindita; Roedi Irawan (Media Gizi Indonesia, 2020)
Obesity causes low-grade chronic infl ammation. Adiponectin is an anti-infl ammatory cytokine. Increased waist circumference in obesity infl uences pro-infl ammatory and anti-infl ammatory cytokine levels which increase the risk of metabolic complications. This study was a cross-sectional study conducted at the Nutrition and Metabolic Diseases Clinic of Children's Hospital Dr. Soetomo, Surabaya. Subjects were chosen consecutively as many as 59 obese adolescents with inclusion criteria: obesity, aged 13-16 years, and having parents / guardians who were willing to follow the research and exclusion criteria: taking drugs, such as dyslipidemia, getting hormone therapy, suff ering from secondary obesity , suff ers from endocrine abnormalities, and has an infection or infl ammatory disease. Anthropometric examination was performed on subjects, including body weight, height, and waist circumference. Body Mass Index (BMI) is measured by weight calculation (kg) divided by height squared (meters) and plotted into the CDC 2000 curve. Obesity is established if a Body Mass Index/Age (BMI/A) >P95 is obtained according to age and sex on the CDC 2000 curve. Adiponectin levels are examined using venous serum with ELISA. The relationship between waist circumference and adiponectin levels was analyzed by Pearson correlation. 59 subjects were included in this study. The mean of waist circumference and adiponectin were 100.18 ± 10.63 cm and 7,84 ± 3,81 μg / ml. Statistic test showed that there is no correlation between waist circumference and adiponectin levels in obese adolescents (p>0,05). There is no correlation between waist circumference and adiponectin levels in obese adolescents. Factors that aff ect the correlation between waist circumference and adiponectin include race, diet and physical activity